Methodological issues in descriptive environmental epidemiology. The example of study Sentieri - Ciocan, Catalina; Franco, Nicolò; Pira, Enrico; Mansour, Ihab; Godono, Alessandro; Boffetta, Paolo (La Medicina del Lavoro, 2021)
Background: Descriptive epidemiology identifies associations between environmental exposures and health effects that require results from methodologically stronger studies before causation can be considered. Objective: To critically review the methodology and results of Sentieri, a descripitive study on residence in areas with one or more industrial source of pollution. Methods: We systematically reviewed the literature quoted by Sentieri for the selection of health effects of nine types of pollution sources of a-priori interest. We also reviewed and meta-analyzed the results of the first report of Sentieri, that analyzed mortality in 44 polluted sites (PS), and 17 causes of deaths during 1995-2002. Results: Among 159 study results quoted by Sentieri, 23.9 % were supportive of an association between residence near a pollution source and a health effect, 30.2 % were partially supportive, 10.7 % were not supportive, and 35.2 % were not relevant. Among 653 standardized mortality ratios for associations between PS-specific pollution sources and causes of death, 14.4% were significantly above 1.02, and 9.0% were significantly below 0.98. Among 48 meta-analysis, seven were significantly above 1.0, including five on exposure to asbestos. Conclusions: Sentieri exemplifies the limitations of descriptive environmental epidemiology studies, in which most hypotheses have limited prior support, most results do not show associations, data on potential confounders and other sources of bias are not available. Such studies tend to replicate well-known associations and occasionally can identify critical situations requiring more investigation, but cannot be used to infer causality either in general or in specific circumstances.